Decision Making Framework Supported By Knowledge Management Activities - Noman, Marwan Hesham (2011)
This research is going to help the managers\' managerial thinking by providing a new framework of decision making techniques. The techniques are available through books, articles and journals, but the key is how to the organization combine these methods into one framework and get mixture of decision making methods.